Health service use by same-sex attracted Australian women for alcohol and mental health issues: a cross-sectional study. Issue 2 (2018) - McNair, Ruth; Pennay, Amy; Hughes, Tonda L; Love, Scarlet; Valpied, Jodie; Lubman, Dan I
No abstract available